Effects of Signal Disruption Depends on the Substrate Preference of the Lactonase - Mahan, Kathleen; Martinmaki, Ryan; Larus, Isabel; Sikdar, Rakesh; Dunitz, Jordan; Elias, Mikael (Frontiers in Microbiology, 2020)
Many bacteria produce and use extracellular signaling molecules such as acyl homoserine lactones (AHLs) to communicate and coordinate behavior in a cell-density dependent manner, via a communication system called quorum sensing (QS). This system regulates behaviors including but not limited to virulence and biofilm formation. We focused on Pseudomonas aeruginosa, a human opportunistic pathogen that is involved in acute and chronic lung infections and which disproportionately affects people with cystic fibrosis. P. aeruginosa infections are becoming increasingly challenging to treat with the spread of antibiotic resistance. Therefore, QS disruption approaches, known as quorum quenching, are appealing due to their potential to control the virulence of resistant strains. Interestingly, P. aeruginosa is known to simultaneously utilize two main QS circuits, one based on C4-AHL, the other with 3-oxo-C12-AHL. Here, we evaluated the effects of signal disruption on 39 cystic fibrosis clinical isolates of P. aeruginosa, including drug resistant strains. We used two enzymes capable of degrading AHLs, known as lactonases, with distinct substrate preference: one degrading 3-oxo-C12-AHL, the other degrading both C4-AHL and 3-oxo-C12-AHL. Two lactonases were used to determine the effects of signal disruption on the clinical isolates, and to evaluate the importance of the QS circuits by measuring effects on virulence factors (elastase, protease, and pyocyanin) and biofilm formation. Signal disruption results in at least one of these factors being inhibited for most isolates (92%). Virulence factor activity or production were inhibited by up to 100% and biofilm was inhibited by an average of 2.3 fold. Remarkably, the treatments led to distinct inhibition profiles of the isolates; the treatment with the lactonase degrading both signaling molecules resulted in a higher fraction of inhibited isolates (77% vs. 67%), and the simultaneous inhibition of more virulence factors per strain (2 vs. 1.5). This finding suggests that the lactonase AHL preference is key to its inhibitory spectrum and is an essential parameter to improve quorum quenching strategies.